Peningkatan Kualitas Pembelajaran Melalui Kemitraan Dosen dan Guru - Endah Hendarwati; Yarno Yarno; Naili Saida (Universitas Muhammadiyah Surabaya, 2019)
The assignment of lecturers to schools aims to improve the quality of learning. The implementation of Lecturer-to-School Assignment conducted at Kalijudan 01/59 Elementary School, Muhammadiyah 10 Junior High School, Baitussalam Junior High School, and Muhammadiyah 7 Senior High School of Surabaya provided many experiences for lecturers of FKIP UMSurabaya and partner school teachers. Differences in perceptions between lecturers and teachers can be understood and straightened out by the existence of lecturer assignment activities to schools. With the assignment of lecturers to the school lecturers and teachers can collaborate with each other to compile an activity plan by seeing and experiencing firsthand experience how to teach in schools with various problems. Lecturers and teachers exchange experiences in learning activities so that learning is more meaningful. Planned and sustainable school assignment activities have a positive impact on FKIP UMSurabaya and partner schools and for improving the quality of education in the Indonesian nation. Learning model innovations and varied media use in learning activities conducted by lecturers can provide motivation to teachers and students in the learning process. With the assignment of lecturers to school this can improve student learning outcomes.